Sosialisasi Kewirausahaan Untuk Meningkatkan Motivasi Ibu-Ibu PKK Desa Jelok Cepogo - Al Hakim, Rosiana Farkhah; Setiawati, Donna; Purwanto, Hari; Ulumuddin, Bahrul; Abdul Latif, Dicky; Hartanto, Hartanto; Nurjanah, Agustina Midya; Ngaeni, Riyatun; Kusuma, Audrey Putri Nabila; Athariq, Luqman; Anjarwati, Dwi; AP, Yulianto (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
Family Welfare Empowerment (PKK) has an important role in empowering families with the aim of improving family welfare and the quality of life of the community. PKK can be at the forefront in overcoming various problems that occur in society by mobilizing PKK women. The aim of implementing this service is to introduce entrepreneurship, provide ideas and motivation to start entrepreneurship or independent business. The method used is material presentation, discussion and question and answer and uses a Participatory Action Research (PAR) approach. The success of this activity was demonstrated by the positive response from the participants as seen by the warm discussions in order to increase the motivation or desire of the PKK women in Jelok village to start entrepreneurship. Assistance is provided until they are able to find the type of business they are interested in.